0768 A Million Dreams: Improving Compliance and Treatment of Obstructive Sleep Apnea via Upper Airway Stimulation Therapy. Real-World Outcomes. (25th May 2022) - Goss, Deborah; Ashtyani, Fariborz; Ashtyani, Laura; Martinez, Maria; Leadley, Lauri; Patterson, Patricia; Moore, David; Stevens, Damien; Faber, Kevin; Lee, Kent; Araujo, Matheus
Abstract: Introduction: Patient compliance to continuous positive airway pressure (CPAP) has been about 50% at 4-years despite numerous improvements in mask design, flow algorithms, education, and monitoring software. Compliance, however, is not equivalent to efficacy. Upper Airway Stimulation (UAS) is an alternative for select CPAP intolerant patients. We used a patient management platform to track UAS compliance and efficacy. Methods: Anonymized, aggregated device usage and outcomes data was analyzed from a HIPAA compliant patient management platform (Inspire Cloud, Inspire Medical Systems, Golden Valley MN) through October 2021. Demographic data is not collected. We used this database to understand therapy outcomes. Data are presented as mean and standard deviation, unless otherwise noted. Results: There were 1.74 million usage nights for 5, 709 patients across 550 clinics. Patients increased median stimulation amplitude from 1.4 to 2.2 volts between activation to 90 days after activation. Typical therapy was activated at 11:44pm, and turned off at 5:51am, with one 13-minute pause per night, and therapy was on 89% of nights.Usage was 5.5 ± 1.8 hours per nights overall, and 6.0 ± 1.9 hours per night used. At 90 days, 90% of patients had usage > 4 hours per nights overall, and 96% had usage > 4 hours per night used.Average pre-implant AHI was reduced from 35 ± 15 events/hour (n=2760), to 9 ± 12 (n=1609) after therapy. ESS was reduced from 11 ± 5 (n=1254) to 7 ± 5 (n=1164). Conclusion: This data represents the first big-data reporting of UAS therapy usage in general clinical practice including nightly data. It demonstrates high nightly usage with minimal pauses and marked improvement in symptoms. It demonstrates the potential that CPAP intolerant patients with can be fully adherent with alternative therapy. Support (If Any): Statistical support provided by Inspire Medical systems.